2015
DOI: 10.1364/oe.23.002647
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of energy transfer for passively Q-switched laser ignition

Abstract: Miniaturized passively Q-switched Nd:YAG/Cr 4+ :YAG lasers are promising candidates as spark sources for sophisticated laser ignition. The influence of the complex spatial-temporal pulse profile of such lasers on the process of plasma breakdown and on the energy transfer is studied. The developed measurement technique is applied to an open ignition system as well as to prototypes of laser spark plugs. A detected temporal breakdown delay causes an advantageous separation of plasma building phase from energy tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In combination with a vacuum chamber, the complex spatial–temporal pulse profile can be detected. Figure 3(a) shows “snap shots” of such a temporal pulse profile calculated from experimental data of Lorenz et al 30 Figure 3(b) illustrates the plasma breakdown at 0.4 MPa occurring delayed to the maximum power density (2.07 × 10 16 W/m 2 ). The temporal delay is measured with a resolution <100 ps and is defined as a breakdown delay (BD).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with a vacuum chamber, the complex spatial–temporal pulse profile can be detected. Figure 3(a) shows “snap shots” of such a temporal pulse profile calculated from experimental data of Lorenz et al 30 Figure 3(b) illustrates the plasma breakdown at 0.4 MPa occurring delayed to the maximum power density (2.07 × 10 16 W/m 2 ). The temporal delay is measured with a resolution <100 ps and is defined as a breakdown delay (BD).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…High temporal and spatial resolution of the complex beam profile. This quantitative method is already published in the study by Lorenz et al 30 Therewith, the energy transfer is obtained from the transmitted laser pulse profile. In combination with a vacuum chamber, the complex spatial-temporal pulse profile can be detected.…”
Section: Characterization Of Energy Transfermentioning
confidence: 99%
“…To determine the transferred energy of laser into plasma at different laser pulse energies and focusing parameters, the same experimental setup as applied by Lorenz et al [21] is used. In Fig.…”
Section: Measurement Of Energy Transfermentioning
confidence: 99%
“…However, the center of the beam profiles can be assumed as radially symmetric, even for laser beams with 9.0 mJ* pulse energy. Lorenz et al [21] have recently demonstrated that the outer areas of laser pulses from end pumped passively q-switched lasers are emitted later in time than inner areas. Furthermore, the beam quality factor M 2 does not take the spatial-temporal emission profile of the laser pulse into consideration.…”
Section: Energy Transfermentioning
confidence: 99%
See 1 more Smart Citation